1997
DOI: 10.1063/1.365629
|View full text |Cite
|
Sign up to set email alerts
|

Intense ion beam optimization and characterization with infrared imaging

Abstract: We have developed two-dimensional calorimetry with infrared imaging of beam targets to optimize and measure the energy-density distribution of intense ion beams. The technique, which measures a complete energy-density distribution on each machine firing, has been used to rapidly develop and characterize two very different beams—a 400 keV beam used to study materials processing and an 80 keV beam used for magnetic fusion diagnostics. Results of measurements, using this technique, varying the diode applied magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 14 publications
2
18
0
1
Order By: Relevance
“…In our conditions incident beam energy is less then ablation threshold for the stainless steel target, so the ablation is not significant for the ion beam energies below 4 J/cm 2 . This corresponds to the results obtained by Davis et al [17] for a diode with an external magnetic insulation of similar design. As stated in [18] the Faraday cup data agree with the infrared data up to 3 J/cm 2 .…”
Section: Measurement Of the Ion Beam Energy Densitysupporting
confidence: 89%
“…In our conditions incident beam energy is less then ablation threshold for the stainless steel target, so the ablation is not significant for the ion beam energies below 4 J/cm 2 . This corresponds to the results obtained by Davis et al [17] for a diode with an external magnetic insulation of similar design. As stated in [18] the Faraday cup data agree with the infrared data up to 3 J/cm 2 .…”
Section: Measurement Of the Ion Beam Energy Densitysupporting
confidence: 89%
“…When the beam energy density exceeds the ablation threshold of the target, the energy absorbed by the target is less than the incident beam energy because some energy is carried away in the ablated material. 8 This leads to an underestimation of the beam energy density when measured by infrared imaging diagnostic, which also affects the results of statistics. We expect that reduction in the energy density on target so that it does not exceed the ablation threshold of the target would increase the variation in energy density.…”
Section: Resultsmentioning
confidence: 98%
“…The magnetic induction in the electron drift region (for the diode with magnetic self-insulation) is comparable with the magnetic induction in a diode with an external magnetic insulation, where an efficiency of ion current generation of over 80% of the total current was achieved. 4 Figure 8 shows the results of a study of homogeneity of the electron beam generation in a flat diode.The distribution of energy density was measured by means of a thermal imaging technique 16 adapted to the double-pulse mode. Experimental studies have shown that, in the diode with magnetic self-insulation, the plasma forms effectively on the entire working surface of the potential electrode and the PIB generation is fairly homogeneous.…”
Section: Analysis Of the Change In Magnetic Insulation Over The mentioning
confidence: 99%